Identification of a Male Sterile Candidate Gene in Lilium x formolongi and Transfer of the Gene to Easter Lily (L. longiflorum) via Hybridization - Moriyama, Takahiro; Shea, Daniel John; Yokoi, Naoto; Imakiire, Seiro; Saito, Takaaki; Ohshima, Hikaru; Saito, Hina; Okamoto, Satoru; Fukai, Eigo; Okazaki, Keiichi (Frontiers in Plant Science, 2022)
Pollen-free varieties are advantageous in promoting cut-flower production. In this study, we identified a candidate mutation which is responsible for pollen sterility in a strain of Lilium × formolongi, which was originally identified as a naturally occurred male-sterile plant in a seedling population. The pollen sterility occurred due to the degradation of pollen mother cells (PMCs) before meiotic cell division. Genetic analysis suggested that the male-sterile phenotype is attributed to one recessive locus. Transcriptome comparison between anthers of sterile and fertile plants in a segregated population identified a transcript that was expressed only in pollen-fertile plants, which is homologous to TDF1 (DEFECTIVE in TAPETAL DEVELOPMENT and FUNCTION1) in Arabidopsis, a gene encoding a transcription factor AtMYB35 that is known as a key regulator of pollen development. Since tdf1 mutant shows male sterility, we assumed that the absence transcript of the TDF1-like gene, named as LflTDF1, is the reason for pollen sterility observed in the mutant. A 30 kbp-long nanopore sequence read containing LflTDF1 was obtained from a pollen-fertile accession. PCR analyses using primers designed from the sequence suggested that at least a 30kbp-long region containing LflTDF1 was deleted or replaced by unknown sequence in the pollen-sterile mutant. Since the cross between L. × formolongi and Easter lily (L. longiflorum) is compatible, we successfully introgressed the male-sterile allele, designated as lfltdf1, to Easter lily. To our knowledge, this is the first report of molecular identification of a pollen-sterile candidate gene in lily. The identification and marker development of LflTDF1 gene will assist pollen-free lily breeding of Easter lilies and other lilies.